2014
DOI: 10.1016/j.jped.2014.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear abnormalities in cells from nasal epithelium: a promising assay to evaluate DNA damage related to air pollution in infants

Abstract: The assay proposed here is suitable for assessing the frequency of nuclear abnormalities from nasal cells in infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Conversely, this study design did not allow to compare the MN and comet test results at high and low air pollutants levels. Various studies found a positive association between air pollution and DNA damage tests at lower levels of air pollutants than that found in our study [40][41][42][43][44][45][46][47][48][49]. However, other studies provided negative or inconsistent results regarding the association between MN frequency in children's cells and air pollutant exposure, highlighting the role of other behavioural factors in the MN occurrence [47,52,53].…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Conversely, this study design did not allow to compare the MN and comet test results at high and low air pollutants levels. Various studies found a positive association between air pollution and DNA damage tests at lower levels of air pollutants than that found in our study [40][41][42][43][44][45][46][47][48][49]. However, other studies provided negative or inconsistent results regarding the association between MN frequency in children's cells and air pollutant exposure, highlighting the role of other behavioural factors in the MN occurrence [47,52,53].…”
Section: Discussionsupporting
confidence: 47%
“…A previous study conducted on preschool children (3-6 years old) living in the same town [39] during two consecutive winters, also found a high mean MN frequency in children's buccal mucosa cells, similarly to that found in present study. Other studies evaluated the frequency of MN in exfoliated buccal cells in children [40][41][42][43][44][45][46][47][48][49] and found a significant association between MN frequencies and various air pollutants in children exposed to air pollution.…”
Section: Discussionmentioning
confidence: 99%
“…The danger of these radiation types primarily originates from their high penetration and ionization energy, which can destroy normal human cells and lead to gene mutation. Long-term exposure to nuclear radiation causes immune decline, cancer, and even immediate death, among other problems, in humans [ 8 , 9 , 10 , 11 , 12 ]. Thus, the effective radiation shielding of nuclear facilities is very important.…”
Section: Introductionmentioning
confidence: 99%
“…In some respiratory disorders, such as asthma and acute viral bronchiolitis, 7 Micronuclei (MN) have been identified as useful markers of cell damage. MN are capable of signaling events associated with cellular and molecular genotoxicity, providing support for a better understanding of etiology and pathogenesis, and consequently for the establishment of prevention strategies.…”
Section: Introductionmentioning
confidence: 99%